(3GdeVGOGJ GdMjhjI s - (3TGgjf, YeQ s; (3TGgjf, QfO s ((3YeGfs (3OGQ GdacQ fGTQh f hehRYhfs, 2008)
(3GdaUd GdGhd (B:(3eHGOF GdYdGL HGdeVGOGJ GdMjhjI GdaUd GdKGfj (B:(3eKHWGJ JTcd GdeVGOGJ GdMjhjI GdaUd GdKGdK(B:(3eKHWGJ JUfjY GdHQhJjfGJ GdaUd GdQGHY(B:(3eVGOGJ GdLQGKje GdYVhjI GdeUfYI GdaUd GdNGeS(B:(3eVGOGJ GdeJaWQGJ GdaUd GdSGOS(B:(3eVGOGJ GdajQhSGJ GdaUd GdSGHY(B:(3eVGOGJ GdaWQjGJ GdaUd GdKGef (B:(3eVGOGJ GdejcQhHGJ GdChdj (B-(3hMjOGJ GdNdjI GdaUd GdJGSY(B:(3eVGOGJ GdWajdjGJ hGdOjOGf agGQS (B1:(3JUfajGJ GdLQGKje (B-(3GdHcJjQjG agGQS(B2:(3JUfjaGJ GdeVGOGJ GdMjhjI hGdehGO GdGNQi GdeSJNOOeI aj GdYdGL MSH GdjI YedgG hWHjYJgG GdcjejGFjIs
Keywords: (3GdeVGOGJ GdMjhjIs